2013
DOI: 10.1364/boe.5.000244
|View full text |Cite
|
Sign up to set email alerts
|

Improved localization accuracy in stochastic super-resolution fluorescence microscopy by K-factor image deshadowing

Abstract: Localization of a single fluorescent particle with sub-diffractionlimit accuracy is a key merit in localization microscopy. Existing methods such as photoactivated localization microscopy (PALM) and stochastic optical reconstruction microscopy (STORM) achieve localization accuracies of single emitters that can reach an order of magnitude lower than the conventional resolving capabilities of optical microscopy. However, these techniques require a sparse distribution of simultaneously activated fluorophores in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The result was compared to a simple TA of the images for the same time period. The K-factor algorithm parameters were chosen according to previous work [24] to be k = 0.9, n = 48, h = 8. Figure 1(a) is the simulated sample with random diffraction limited spots originating from scattering of light from the GNPs with added background noise and shot noise so that the SNR was -20dB.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result was compared to a simple TA of the images for the same time period. The K-factor algorithm parameters were chosen according to previous work [24] to be k = 0.9, n = 48, h = 8. Figure 1(a) is the simulated sample with random diffraction limited spots originating from scattering of light from the GNPs with added background noise and shot noise so that the SNR was -20dB.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…However, in a previous paper [27] we had shown that the first few factors of the decomposition, marked by f h , where h<M, contain most of the image data together with noise, while high order factors contains mostly noise together with some fine spatial information associated with low contrast levels. By multiplying the original image with the first few harmonies, the image data will be de-emphasized in the reconstruction and noise will be reduced.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous paper we suggested the use of the modified K-factor algorithm for the same purpose [35]. The PST has two major advantages in respect to the K-factor algorithm: The first is a larger narrowing of the PSF, by a factor of 2 with compared to the K-factor, resulting in the ability to detect even closer PSFs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The proposed algorithm is a computer post processing technique that can be applied to the raw data prior to emitter localization. In a previous paper, the algorithm was applied to 2D images 22 showing improvement in localization precision or data acquisition time of ~40%. Here we present a modified version, which is applied to 3D localization.…”
mentioning
confidence: 99%